Hubungan Lama Waktu Hemodialisa dengan Tingkat Kecemasan Pada Pasien Gagal Ginjal Kronik di RSUD Kabupeten Bekasi - Vira Alesandra; Cusmarih Cusmarih (Malahayati Nursing Journal, 2024)
ABSTRACT Chronic kidney disease (CKD) is a global public health disorder with an increasing prevalence and incidence of kidney failure, poor prognosis and high treatment costs. The prevalence of chronic kidney disease increases along with the increasing number of elderly population due to degenerative diseases followed by diabetes mellitus and hypertension. About 1 in 10 of the global population has CKD at some stage (Infodatin, 2019). Determine the relationship between hemodialysis time and anxiety levels in CKD patients at Bekasi Bekasi Regency Hospital in 2023. The sample of this study is all patients who are undergoing Hemodialysis at Bekasi Regency Hospital in 2023. With Random Sampling technique. Chi Square test results show that there is a relationship between the length of hemodialysis time and anxiety levels in chronic kidney failure patients at Bekasi Regency Hospital in 2023 as many as 44 respondents and P value results of 0.019(p0.05). There is a relationship between the length of hemodialysis time and anxiety levels in chronic kidney failure patients at Bekasi Regency Hospital in 2023. Keywords: Anxiety Level, Length of Time Hemodialysis. ABSTRAK Penyakit ginjal kronis (PGK) merupakan gangguan Kesehatan masyarakat global dengan prevalensi dan insiden gagal ginjal yang meningkat, prognosis yang buruk dan biaya pengobatan yang tinggi. Prevalensi Penyakit ginjal kronis meningkat seiring meningkatnya jumlah penduduk usia lanjut akibat penyakit degeneratif diikuti oleh penyakit diabetes melitus dan hipertensi. Sekitar 1 dari 10 populasi global mengalami PGK pada stadium tertentu (Infodatin, 2019). Mengetahui hubungan lama waktu hemodialisa dengan tingkat kecemasan pada pasien PGK di RSUD Kabupaten Bekasi Bekasi tahun 2023. Sampel penelitian ini seluruh pasien yang sedang menjalankan Hemodialisa di RSUD Kabupaten Bekasi tahun 2023. Dengan teknik Random Sampling. Hasil uji Chi Square menunjukan bahwa adanya Hubungan lama waktu Hemodialisa dengan tingkat kecemasan pada pasien gagal ginjal kronik di RSUD Kabupaten Bekasi tahun 2023 sebanyak 44 Responden dan hasil P value 0.019(p0.05). Adanya Hubungan lama waktu Hemodialisa dengan tingkat kecemasan pada pasien gagal ginjal kronik di RSUD Kabupaten Bekasi tahun 2023. Kata Kunci: Tingkat Kecemasan, Lama Waktu Hemodialisa